5-hydroxymethylcytosine profiling as an indicator of cellular state. (December 2013) - Laird, Alexander; Thomson, John P; Harrison, David J; Meehan, Richard R
DNA methylation is widely studied in the context of cancer. However, the rediscovery of 5-hydroxymethylation of DNA adds a new layer of complexity to understanding the epigenetic basis of development and disease, including carcinogenesis. There have been significant advances in techniques for the detection of 5-hydroxymethylcytosine and, with this, greater insight into the distribution, regulation and function of this mark, which are reviewed here. Better understanding of the associated pathways involved in regulation of, and by, 5-hydroxymethylcytosine may give promise to new therapeutic targets. We discuss evidence to support the view of 5-hydroxymethylcytosine as a unique and dynamic mark of cellular state. These 5-hydroxymethylcytosine profiles may offer optimism for the development of diagnostic, prognostic and predictive biomarkers.